Physician-scientists in neurology: Research contributions of a cohort of neurologists. (11th September 2018) - Bensken, Wyatt P.; Hansen, Alexandra K.; Norato, Gina; Heiss, John D.; Nath, Avindra; Khan, Omar I.
Abstract : Objective: The objective of this study was to evaluate the methods by which neurology physician-scientists are quantified through applying author-level metrics to commonly used definitions when discussing funding efforts aimed at the attrition of the physician-scientist workforce. Methods: Neurology residency alumni from institutions with the highest National Institute of Neurological Disorders and Stroke funding were identified for 2003–2005, and their funding records, publishing history, and impact factor ( h -index) were obtained via the NIH Research Portfolio Online Reporting Tools and Scopus Author Profile. The group differences of total publications, yearly publication rate, and h- index between R01-funded, non-R01-funded, and nonfunded individuals were analyzed via analysis of variance models, and a publications-per-research hour rate was calculated and similarly compared across groups. Results: From 15 programs, and from a total of 252 neurologists, 186 were identified as having demonstrated an interest in research. The mean h- index, yearly publication rate, and cumulative number of publications were significantly higher in those who eventually received an R01 grant compared to those without R01 funding and those with no research funding. Within the top 50 performers by yearly publication rate, there was an equal mix of the 3 groups of neurologists: R01 (19, 38%), non-R01 (15, 30%), and nonfunded (16, 32%). Those who were nonfunded (10% research effort) had an estimated 4.9 publications per 1, 000 research hours compared to 3.0 for those with non-R01 (40% research effort) funding and 3.2 for those with R01 funding (80% research effort). Conclusions: While eventual R01 grant and early career funding pathways were confirmed as important components of higher h -index and larger publication numbers, the classic definition of a physician-scientist was questioned through these findings. Those presumed to be without funding and generally excluded from the physician-scientist pool because of lack of protected research time, in some instances, outperformed their R01-funded colleagues and had a higher publications-per-research hour than those with an R01 and those with non-R01 funding, when estimating a 10% research effort. This reflects a potentially erroneous assumption and indicates the important contribution of these neurologists.